Cancer-associated fibroblasts activated by miR-196a promote the migration and invasion of lung cancer cells. (28th June 2021) - Lee, Sieun; Hong, Ji Hyung; Kim, Jeong Seon; Yoon, Jung Sook; Chun, Sang Hoon; Hong, Soon Auck; Kim, Eun Ju; Kang, Keunsoo; Lee Kang, Jihee; Ko, Yoon Ho; Ahn, Young-Ho
Abstract: Fibroblasts in the tumor microenvironment, known as cancer-associated fibroblasts (CAFs), promote the migration, invasion, and metastasis of cancer cells when they are activated through diverse processes, including post-transcriptional regulation by microRNAs (miRNAs). To identify the miRNAs that regulate CAF activation, we used NanoString to profile miRNA expression within normal mouse lung fibroblasts (LFs) and CAFs. Based on NanoString profiling, miR-196a was selected as a candidate that was up-regulated in CAFs. miR-196a-overexpressed LFs (LF-196a) promoted the migration and invasion of lung cancer cells in co-culture systems (Transwell migration and spheroid invasion assays). ANXA1 was confirmed as a direct target of miR-196a, and adding back ANXA1 to LF-196a restored the cancer cell invasion promoted by miR-196a. miR-196a increased CCL2 secretion in fibroblasts, and that was suppressed by ANXA1 . Furthermore, blocking CCL2 impeded cancer spheroid invasion. In lung adenocarcinoma patients, high miR-196a expression was associated with poor prognosis. Collectively, our results suggest that CAF-specific miR-196a promotes lung cancer progression in the tumor microenvironment via ANXA1 and CCL2 and that miR-196a will be a good therapeutic target or biomarker in lung adenocarcinoma. Highlights: CAF-specific miR-196a promotes the migration and invasion of lung cancer cells. The effect of miR-196a is medicated by ANXA1 and CCL2. miR-196a is associated with poor survival of lung adenocarcinoma patients. miR-196a will be a good therapeutic target in lung adenocarcinomas.